Hospital doctors in Ireland and the struggle for work–life balance. (19th September 2020) - Humphries, Niamh; McDermott, Aoife M; Creese, Jennifer; Matthews, Anne; Conway, Edel; Byrne, John-Paul
Abstract: Ireland has a high rate of doctor emigration. Challenging working conditions and poor work–life balance, particularly in the hospital sector, are often cited as a driver. The aim of this study was to obtain insight into hospital doctors' experiences of work and of work–life balance. In late 2019, a stratified random sample of hospital doctors participated in an anonymous online survey, distributed via the national Medical Register (overall response rate 20%; n = 1070). This article presents a qualitative analysis of free-text questions relating to working conditions ( n = 469) and work–life balance ( n = 314). Results show that respondent hospital doctors, at all levels of seniority, were struggling to achieve balance between work and life, with work–life imbalance and work overload being the key issues arising. Work–life imbalance has become normalized within Irish hospital medicine. Drawing on insights from respondent hospital doctors, this study reflects on the sustainability of this way of working for the individual doctors, the medical workforce and the Irish health system. If health workforce planning is about getting the right staff with the right skills in the right place at the right time to deliver care, work–life balance is about maintaining doctor wellbeing and encouraging their retention.